CONTROLLABILITY RESULTS FOR SECOND ORDER IMPULSIVE NEUTRAL FUNCTIONAL INTEGRODIFFERENTIAL INCLUSIONS WITH INFINITE DELAY - Samuel, F. Paul; Gunasekar, T.; Arjunan, M. Mallika (Italian Journal of Pure and Applied Mathematics, 2013)
This paper is concerned with the controllability of a partial neutral functional integrodiﬀerential inclusion of second order with impulse eﬀect and infinite delay in Banach spaces. The controllability of mild solutions using a fixed point theorem for contraction multi-valued maps and without assuming compactness of the family of cosine operators.